WSN-based reconfigurable water quality monitoring system in IoT environment - Myint, C.; Gopal, Lenin; Aung, Y. (2017)
© 2017 IEEE. In internet of things (IT) environment, a sensor interface device is essential for data collection in wireless sensor network (WSN) system for water quality monitoring (WQM) as the water pollution is a critical issue globally. This paper presents the design of a WSN based reconfigurable smart sensor interface device for WQM system in an IoT environment. The system consists of Field Programmable Gate Array (FPGA) design board, sensors, ZigBee based wireless communication module and personal computer (PC). The FPGA board performs as the heart of the proposed WQM system and it is programmed in very high speed integrated circuit hardware description language (VHDL) and C++ using Qsys tool and Nios-II SBT for Eclipse in Quartus II software. The proposed system collects the data of water quality such as water pH, water level, turbidity, carbon dioxide (CO 2 ) on the surface of water and water temperature in parallel and in real-time basis with high speed from five different sensor nodes. The performance of the proposed reconfigurable WSN system is verified through computer simulation and laboratory experiments.